(untitled) (Applied Biological Research, 2025)
Conservation agriculture (CA) based zero-tillage system has gained prominence for its potential to improve soil health, enhance nutrient cycling, and increase carbon sequestration in soil. Knowledge about the changes in soil carbon and nitrogen dynamics under no-tillage and different cropping systems is necessary to assess the feasibility of adopting conservation agriculture to sustain soil health and productivity. This study compared conventional tillage (CT) and zero-tillage (ZT) systems, and three cropping systems (soybean-wheat, maize-wheat and maize-chickpea) on soil carbon and nitrogen dynamics. The experiment was established in 2010 on a Vertisol in Bhopal, India. After the completion of the 14th cycle of the experiment (2023-24), soil samples were collected from each plot and analysis processes were executed. The soil under ZT had found significantly higher concentrations of soil organic carbon (0.93%), total organic carbon (1.23%), very labile pool (0.55%), labile pool (0.19%), non-labile (0.36%) and total carbon (1.39%) than CT at 0-10 cm depth. Available nitrogen (229.83 kg ha1) and total nitrogen (0.133%) also had significantly higher in ZT than CT at surface soil. Tillage and cropping systems had no significant impact on soil inorganic carbon and mineral nitrogen (ammonium and nitrate nitrogen). Therefore, under Vertisols, 14 years of ZT practices are likely to improve organic carbon concentration and increase the availability of nitrogen in soil, allowing a positive trend for soil preservation and carbon sequestration in soil.